Optimization of Operating Conditions for the Extraction of Natural Dyes, from the Peel of Djenkol (Pithecellobium Jiringa) Using the Response Surface Methodology (RSM) Method and Behnken Design (BBD) Experimental Design - Utami, Herti; Marlina, Arlin; Azizah, Ara Annastasya; Nurhidayat, Adib (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Natural dyes are generally contained in plant parts such as twigs, stems, peel, flowers, fruits, and roots. Djenkol peel is one of the wastes that has the potential to be used as a natural dye. The extraction of natural dyes from djenkol peel is carried out using Ultrasonic Assisted Extraction. Optimization was carried out using the Response Surface Methodology (RSM) with an experimental design of Box Behnken Design (BBD) which aimed to determine the influence of three research variables (solid to liquid ratio, time, and extraction temperature) on the yield response of the obtained natural dye extract. Based on the optimization that has been carried out, an optimal solution was obtained with an optimal %yield result from the natural dye extract of djenkol peel of 25.285% with variations of solid to liquid ratio, temperature, and extraction time respectively of 0.079 g/ml, 59.979 oC, and 89.998 minutes. The results of the UV-Vis spectrophotometry test showed a wave peak at 300 nm with an absorbance value of 4.88, the GC-MS test showed that tannin are the dominant compounds contained in djenkol peel extract.